Perbandingan Metode Altman Z-Score, Grover, Springate, dan Zmijewski dalam Memprediksi Financial Distress pada Perusahaan Sektor Pertanian yang Terdaftar Di Bursa Efek Indonesia - Nyanyu Mita Pratiwi; Hidayat Wiweko (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
This research purpose to determine the most accurate models among Altman, Grover, Springate and Zmijewski to predict the financial distress on agriculture companies listed on Indonesia Stock Exchange (IDX) for the 2017-2019 period. The population in this research is the agriculture companies listed on the Indonesia Stock Exchange for the 2017-2019 period, which are 25 companies. Based on the purposive sampling method, a sample of 24 companies was obtained. This research used the accuracy test and determinant coefficient. The result showed Springate is the most accurate model to predict the financial distress, the second is Grover and than Altman and Zmijewski.